Bona vacantia in West Malaysia: issues and challenges - Abdullah Sanek, Siti Khadijah; Halim, Akmal Hidayah; Mohd Salim, Wan Noraini; Drs Nasrul, Muhammad Amrullah (Global Academic Excellence (M) Sdn Bhd, 2024)
This paper examines the concept of bona vacantia, or ownerless goods, in West Malaysia, probing into legal, practical, and societal perspectives. It highlights the differences in handling these assets under Islamic law (Sharia) for Muslims and civil law for non-Muslims, with the former reverting ownerless assets to Baitulmal and the latter managing them through the federal government or state authority. This paper highlights the inefficiencies and inconsistencies in bona vacantia administration, which leads to fragmented legal provisions, administrative variances, and challenges for small estate claims. Furthermore, a lack of data on ownerless estates exacerbates these problems. It thoroughly analyses the legal framework, issues and challenges using a qualitative approach, based on a literature review and interview with the Unclaimed Money Management Division (BWTD). The study was also conducted using a library research approach, incorporating qualitative exploratory and descriptive methodologies. Data analysis was performed through content analysis. Bibliographic references encompass information obtained from various mediums including journals, conference proceedings, and online media. The conclusion advocates the need for collaborative efforts among stakeholders to address these challenges and develop standardised procedures and policies. The integration of multiple disciplines is essential for developing efficient strategies and solutions to handle ownerless properties. We anticipate that this collaborative endeavour will be a critical milestone in addressing the complexities of bona vacantia management.